Modeling an Optical Network Operating with Hybrid-Switching Paradigms - Luiz Henrique Bonani (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract The continuous increasing of the Internet traffic has brought serious concerns about capacity exhaustion of the optical infrastructure in a medium term horizon. Taking into account the optical networks, comprising the Internet backbone, the strategies to avoid this catastrophic scenario point to the development of new technologies that enable the capacity expansion, as well as to a better utilization of network resources (spectrum or wavelengths). The elastic optical network, considered as a realistic perspective for the infrastructure, optimizes the required spectrum and improve the efficiency of resources utilization. However, it is based on optical circuit switching paradigm that tends to waste resources due to idle times of reservation process. Since in some dedicated optical networks, like data center networks, certain optical switching paradigms have become reality, it is expected that in the coming years not only an elastic optical network, but also a hybrid network, in terms of switching paradigms, be brought to reality. Considering this scenario, the present paper addresses some issues on the modeling of an optical network working with hybrid-switching paradigms.